Enhanced piezoelectric properties of PVdF-HFP/PZT nanocomposite for energy harvesting application - Oumghar, K; Chakhchaoui, N; Farhane, R; Eddiai, A; Meddad, M; Cherkaoui, O; Van Langenhove, Lieva (IOP conference series. Materials Science and Engineering, 2020)
The use of piezoelectric nanocomposite in detection and actuation applications for the development of electromechanical microsystems (MEMS) has become quite common over the last decade. In this paper, we present a flexible piezoelectric nanocomposite films, composed of lead zirconate titanate (PZT) nanoparticles, embedded in poly(vinylidene-difluoride hexafluoro propylene) (PVdF-HFP) matrix. Piezoelectric and ferroelectric properties evolution is proportional to the evolution of the crystalline β-phase. The evaluation of the interactions between PZT and PVdF- HFP, performed by Fourier transform infrared spectroscopy (FTIR), revealed a dramatic improvement in these characteristics over pure PVdF-HFP, and attributed to a better crystallinity of the PVdF-HFP matrix and uniform distribution of nanoparticles. These films nanocomposites were done by solvent casting method, with various concentrations of PZT. Results of these experiments indicate that the investigated thin films nanocomposites are appropriate for various applications in energy storage and energy harvesting application.